Uplifting School Leadership—Enabling Structures and Processes: The Seven Powers of the Townsend/Adams Approach - Boyd, William Edgar (Alberta Journal of Educational Research, 2021)
This article reviews the work of two Albertan educators, David Townsend and Pam Adams, in their application of collaborative inquiry to improving school leadership. Collaborative inquiry is essentially a professional practice that has yet not been comprehensively theorized. This article seeks to lay some foundations for a theorization of the practice by identifying structures and processes that appear to underlie the remarkable success of applications of the practice in several school districts in Alberta, Canada. The emerging mode is one that envisages seven powers: the power of teams, the power of relationship, the power of the process, the power of inquiry and reflection, the power of collaboration, the power of modelling, and the power of narrative. These powers appear to underpin much of what has been written about the ways in which collaborative inquiry has become a powerful force for leadership development in Alberta, and more recently in the State of New South Wales in Australia. Keywords: Collaborative inquiry, school leadership, enabling structures Cet article examine le travail de deux éducateurs albertains, David Townsend et Pam Adams, dans leur application de l'enquête collaborative pour améliorer le leadership scolaire. L'enquête collaborative est essentiellement une pratique professionnelle qui n'a pas encore été théorisée de manière exhaustive. Cet article cherche à jeter les bases d'une théorisation de la pratique en identifiant les structures et les processus qui semblent sous-tendre le succès remarquable des applications de la pratique dans plusieurs districts scolaires de l'Alberta, au Canada. Le mode émergent est celui qui envisage sept pouvoirs : le pouvoir des équipes, le pouvoir des relations, le pouvoir du processus, le pouvoir de l'enquête et de la réflexion, le pouvoir de la collaboration, le pouvoir de la modélisation et le pouvoir du récit. Ces pouvoirs semblent sous-tendre une grande partie de ce qui a été écrit sur la manière dont l'enquête collaborative est devenue une force puissante pour le développement du leadership en Alberta, et plus récemment dans l'État de Nouvelle-Galles du Sud en Australie. Mots clés : enquête collaborative, leadership scolaire, structures habilitantes